INVESTIGATION OF REACTION ABILITY OF α-HALOGENOCARBONIC ACIDS WITH UNSATURATED ALCOHOLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
It has been shown that the rate of reaction in case of α-alkyl-α-bromacetic acid is 1.45–1.5 times higher, than for α-alkyl-α-chloroacetic acids. The influence of a-alkyl substitute on the rate of formation of goaled product has been studied.